Application of the PEE model to essay composition in an IELTS preparation class - Velasco Tovar, Ender Orlando (Colombian Applied Linguistics Journal, 2015)
Based on two case studies, this study investigates the application of the Point, Explanation, Example (PEE) model to essay composition in a multi-lingual IELTS preparation class. This model was incorporated into an eight-week programme of instruction to ESL adults in London, England. Students preparing for the IELTS exam were asked to write pre- and post-instruction essays on a given topic within 40 minutes. Employing the IELTS band descriptors (IELTS, 2013) and analyses of coherence and cohesion in line with Systemic Functional Linguistic concepts (Halliday & Matthiessen, 2004; McCarthy, 1991), samples of students’ writing were analysed. Data from students’ pre- and post-instruction interviews was also gathered and analysed. The findings of this study suggest that the PEE model is to some extent effective in improving the essay composition performance of IELTS students, in particular in the area of cohesion and coherence. Students find the PEE model useful in regard to the clarity and structure that the model seems to add to their essays.